2013
DOI: 10.1155/2013/460437
|View full text |Cite
|
Sign up to set email alerts
|

A Crosslinked HA-Based Hydrogel Ameliorates Dry Eye Symptoms in Dogs

Abstract: Keratoconjunctivitis sicca, commonly referred to as dry eye or KCS, can affect both humans and dogs. The standard of care in treating KCS typically includes daily administration of eye drops to either stimulate tear production or to hydrate and lubricate the corneal surface. Lubricating eye drops are often applied four to six times daily for the life of the patient. In order to reduce this dosing regimen yet still provides sufficient hydration and lubrication, we have developed a crosslinked hydrogel based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
36
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 29 publications
2
36
0
1
Order By: Relevance
“…Thus, crosslinked CMHA-S would act as a local lubricant as well as a highly biocompatible vehicle to deliver drugs in a sustained manner with less frequent ocular administration. 13,33,34 Such drugs may include growth factors or small molecules to stimulate Figure 1. An example of crosslinking thiol-modified carboxymethyl hyaluronic acid (CMHA-with thiol-modified gelatin) (Gtn-DTPH) using the bifunctional crosslinker poly(ethylene glycol) diacrylate (PEGDA) to form a thioether crosslinked semi-synthetic matrix (CMHA-GSX).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, crosslinked CMHA-S would act as a local lubricant as well as a highly biocompatible vehicle to deliver drugs in a sustained manner with less frequent ocular administration. 13,33,34 Such drugs may include growth factors or small molecules to stimulate Figure 1. An example of crosslinking thiol-modified carboxymethyl hyaluronic acid (CMHA-with thiol-modified gelatin) (Gtn-DTPH) using the bifunctional crosslinker poly(ethylene glycol) diacrylate (PEGDA) to form a thioether crosslinked semi-synthetic matrix (CMHA-GSX).…”
Section: Discussionmentioning
confidence: 99%
“…33,34,47 For KCS, the studies demonstrated that the CMHA-S gel drops, administered twice to thrice daily, reduced ocular irritation, hyperemia, and discharge, and increased ocular comfort as assessed by pet owners in as little as 2 weeks. Further, the CMHA-S gel was superior in reducing these symptoms compared with a solu- tion of non-crosslinked HA at a similar concentration, and owners were more satisfied with the outcomes when using CMHA-S gel.…”
Section: Clinical Experience To Datementioning
confidence: 99%
“…(Dr Brenda Mann, University of Utah Bioengineering Department, personal communication, 2017) The rheological behaviour of such hyaluronic acid products generally containing relatively short molecules at relatively low concentrations is for the most part Newtonian with an increase in viscosity with shear rate. 33 Research at the University of Utah Department of Bioengineering has investigated crosslinking of hyaluronic acid to create molecules exhibiting shear thinning and thus forming a valuable addition to the panoply of tear replacement medications. To crosslink the molecules a reactive group is first introduced into the molecule by carboxylating hydroxyl groups.…”
Section: Developing a Non-newtonian Tear Replacementmentioning
confidence: 99%
“…Chemical reactions used in formulation of crosslinked carboxymethyl hyaluronic acid (taken from Williams and Mann33 ).…”
mentioning
confidence: 99%
“…B iodegradable films using a carboxymethylated, hyaluronic acid-based polymer (CMHA-S; Jade Therapeutics, Salt Lake City, UT, USA) are proving to be a safe and an effective means of local drug delivery for treatment of ophthalmic conditions. [1][2][3][4] One existing challenge with the development of CMHA-S films for clinical use is its inability to stay on the eye in the lower fornix for extended periods of time. This limited retention hinders drug treatment and healing capacity of the film for use in ophthalmic conditions.…”
mentioning
confidence: 99%